The Conflict Between Greece And Turkey In The Mediterranean Sea (International Maritime Law Study) - YÄ±ldÄ±z, Edanur (Jurnal Hukum, 2020)
Turkey and Greece are again dragged into a new conflict in the East Mediterranean. Turkey and Greece vie for supremacy in the eastern Mediterranean. Turkey, for its part, indicated that Greece's claim to the territory would amount to a siege in the country by giving Greece a disproportionate amount of territory. This study aims to rethink the conflict between Greece and Turkey in the waters of the Mediterranean sea in the view of international maritime law. This study uses an empirical juridical approach. The Result of this research is Turkey does not ignore the Greece rights, Greece ignores the international law with its extended or excessive maritime claims. Greece tries to give full entitlement of the islands in Mediterranean and Agean. Whereas the effect Formula is applied by international courts.